Design of sensible and latent heat thermal energy storage systems for concentrated solar power plants: Thermal performance analysis. (May 2020) - Liu, Ming; Riahi, Soheila; Jacob, Rhys; Belusko, Martin; Bruno, Frank
Abstract: A shell-and-tube design with different thermal energy storage (TES) media was investigated as a promising TES system for a next generation concentrated solar power (CSP) plant. Sensible TES using graphite, latent TES using phase change materials (PCMs) and a hybrid of both were investigated. A two-dimensional transient heat transfer model was applied to simulate the thermal performance of multiple shell-and-tube TES modules connected in series. Considering the realistic operation of the CSP plant, an intensive numerical investigation was conducted to design and size the storage system. The TES systems studied were categorized as 3-PCM cascade, 5-PCM cascade, PCM-graphite-PCM hybrid and single graphite. All the PCMs considered in this paper have been experimentally proven as potential candidate storage media. It was found that all the TES systems studied, if well designed, can meet the CSP operational requirements. In comparison, single graphite storage is less problematic, but it has the lowest storage density (47.3 kWhr/tonne). By forming a PCM-graphite-PCM sandwich configuration, the energy density was increased to 60.9 kWhr/tonne and the storage effectiveness of this hybrid system is 70.7%, the highest among all the TES systems studied. Highlights: A 2D model was validated and verified using experimental and CFD results. Six designs of sensible, latent and sensible-latent hybrid storage were investigated. The overall storage effectiveness of the hybrid design is the highest. The effectiveness of the graphite system is improved by 21.2% in hybrid design.